2017
DOI: 10.1371/journal.pone.0173188
|View full text |Cite
|
Sign up to set email alerts
|

Re-conceptualizing stress: Shifting views on the consequences of stress and its effects on stress reactivity

Abstract: BackgroundThe consequences of stress are typically regarded from a deficit-oriented approach, conceptualizing stress to be entirely negative in its outcomes. This approach is unbalanced, and may further hinder individuals from engaging in adaptive coping. In the current study, we explored whether negative views and beliefs regarding stress interacted with a stress framing manipulation (positive, neutral and negative) on measures of stress reactivity for both psychosocial and physiological stressors.MethodNinet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 27 publications
3
33
1
3
Order By: Relevance
“…Specifically, stress mindset interventions in the future may seek to present a balanced view of stress or that stress can be enhancing. This is supported by the evidence for incremental validity attained in the current study, and is consistent with Liu, Vickers, Reed, and Hadad (2017), who found that presenting videos outlining balanced consequences of stress results in significantly lower heart rates and diastolic blood pressure following a lab-induced stressor than when videos outlining strictly positive or negative consequences of stress are presented.…”
Section: Theoretical and Practical Implicationssupporting
confidence: 91%
“…Specifically, stress mindset interventions in the future may seek to present a balanced view of stress or that stress can be enhancing. This is supported by the evidence for incremental validity attained in the current study, and is consistent with Liu, Vickers, Reed, and Hadad (2017), who found that presenting videos outlining balanced consequences of stress results in significantly lower heart rates and diastolic blood pressure following a lab-induced stressor than when videos outlining strictly positive or negative consequences of stress are presented.…”
Section: Theoretical and Practical Implicationssupporting
confidence: 91%
“…Specifically, in these studies, participants' physiological and subjective stress, and anxiety were assessed both before and after a stressor. The prestressor to poststressor correlation for the physiological data was extracted from Liu, Vickers, Reed, and Hadad (), who found a prestressor to poststressor correlation coefficient for HR of r = 0.837 ( df = 89; p < .001), for SBP of r = 0.803 ( df = 88; p < .001), and for DBP of r = 0.812 ( df = 89; p < .001). For the subjective data, we extracted the data from Linett () and found a correlation coefficient for subjective anxiety of r = 0.543 ( df = 55; p < .001) and for subjective stress, a correlation coefficient of r = 0.733 ( df = 55; p < .001).…”
Section: Methodsmentioning
confidence: 99%
“…Rather than building upon their existing conceptualization to engender a more balanced view of stress, it may result in the video content being rejected altogether. More recent research (20) has found that presenting videos outlining the balanced consequences of stress results in significantly decreased heart rates and diastolic blood pressure following a lab-induced stressor compared to videos outlining strictly positive or negative consequences of stress. We contend that measurement of stress mindsets should be framed to explicitly measure nuanced beliefs about the malleability of the consequences of stress such that stress "can be" enhancing, on the basis of three arguments: (a) the potential benefits of holding a nuanced or balanced view of stress (20), (b) the importance, within mindset theory, of seeing particular traits as malleable (12,13), and (c) the current conceptualization of stress mindsets indicating that stress can be both enhancing and debilitating (5).…”
Section: Theoretical Basis Of a Stress Beliefs Modelmentioning
confidence: 99%
“…First, rather than simply drawing an individual's attention toward the enhancing properties of stress, attention should be drawn to the malleable and controllable nature of the stress response in order to elicit the belief that one is in control of their personal response to stressors. Supporting this assertion, recent research has found that showing a video presenting a balanced conceptualization of stress results in more adaptive physiological outcomes under acute stress in contrast with presentation of an unbalanced-positive or unbalanced-negative conceptualization of stress (20). Second, a recent meta-analysis (55) reviewed 24 university student stress-reduction interventions; all of which required engagement in a cognitive (including mindfulness) or behavioral strategy to deal with the stress.…”
Section: Recommendations For Future Research and Practicementioning
confidence: 99%